2008
DOI: 10.1089/acu.2008.0588
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Carpal Tunnel Syndrome With Medical Acupuncture

Abstract: Background:Conservative management plays an important role in the treatment of carpal tunnel syndrome. Non-surgical options include physical and occupational therapy, splints, steroid injections, yoga, carpal bone mobilization, and anti-inflammatory drugs. Clinical experience demonstrates that acupuncture should be considered among these treatments as it may provide symptomatic relief to patients with this disorder. Objective: To demonstrate an acupuncture protocol for the treatment of carpal tunnel syndrome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…The result of this study was in line with previous research studies. One randomized trial study with long-term follow-up (13 months) compared acupuncture with oral steroids in management of CTS (Naeser, et al, 2002), and another randomized controlled trial study compared efficacy of acupuncture with night splinting (5 weeks) for CTS (Schulman, Liem, and Moroz, 2008). Both studies found that electro-acupuncture was more effective in mild to moderate CTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of this study was in line with previous research studies. One randomized trial study with long-term follow-up (13 months) compared acupuncture with oral steroids in management of CTS (Naeser, et al, 2002), and another randomized controlled trial study compared efficacy of acupuncture with night splinting (5 weeks) for CTS (Schulman, Liem, and Moroz, 2008). Both studies found that electro-acupuncture was more effective in mild to moderate CTS.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is the most familiar complementary and alternative medicine, especially in Chinese medical treatments (World Health Organization, 2002). The efficacy of acupuncture in management of mild to moderate CTS has been investigated in a limited number of studies (Freedman, 2002;Naeser, et al, 2002;Schulman, Liem, and Moroz, 2008), and mixed results have been reported (O'Connor, Marshall, and Massy-Westropp, 2003;Yang, et al, 2009;Ernst, 2009;Kumnerddee and Kaewtong, 2010;Sim. et al, 2011).…”
Section: Cts Can Be Diagnosed By Provocative Clinical Tests Such As Pmentioning
confidence: 99%
“…acupuntura y la electroacupuntura mostrando mejorías en el STC (►Tabla 3). [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] El único estudio introducido que no mostró cambios favorables ha sido el de Yao y colaboradores (►Tabla 3). 43 Estos autores obtuvieron que el grupo de intervención de acupuntura mejoró a los 3 meses de forma idéntica al del grupo placebo.…”
Section: þ Cunclassified
“…Schulman y cols., 200823 (À) ( À)( À) ( À) ( À) ( þ) ( À)Shokunbi, 201424 (À) ( À)( À) ( À) ( À) ( À) ( À) Napadow y cols., 2004 25 (À) ( À) ( À) ( þ) ( þ) ( þ) ( þ) Zailaa, 2010 26 (þ) ( þ) ( À) ( þ) ( þ) ( þ) ( þ) Ding y Shen, 2013 27 (þ) ( þ) ( À) ( À) ( þ) ( þ) ( À) Wong y cols., 2016 28 (þ) ( þ) ( À) ( À) ( þ) ( þ) ( À) Dimitrova y cols., 2019 29 (þ) ( þ) ( À) ( þ) ( þ) ( þ) ( À) Chen y cols., 2017 30 (þ) ( þ) ( À) ( À) ( þ) ( þ) ( À) Ural y Öztürk, 2017 31 (þ) ( þ) ( À) ( À) ( þ) ( þ) ( À) Maeda y cols., 2017 32 (À) ( À) ( À) ( þ) ( þ) ( þ) ( þ)Hadianfard y cols., 201533 (þ) ( þ) ( À) ( À) ( þ) ( þ) ( À) Maeda y cols., 2013a 34 (þ) ( þ) ( À) ( þ) ( À) ( þ) ( À) Ho y cols., 2014 35 (À) ( À) ( À) ( þ) ( þ) ( þ) ( À) Maeda y cols., 2013b 36 (þ) ( þ) ( À) ( À) ( þ) ( þ) ( À) Khosrawi y cols., 2012 37 (þ) ( þ) ( À) ( À) ( À) ( þ) ( þ) Kumnerddee Kaewtong 2010 38 (þ) ( þ) ( À) ( À) ( þ) ( þ) ( þ) Yang y cols., 2011 39 (þ) ( þ) ( À) ( À) ( À) ( þ) ( À) Yang y cols., 2009 40 (þ) ( þ) ( À) ( À) ( À) ( þ) ( À) Napadow y cols., 2007 41 (þ) ( þ) ( þ) ( À) ( þ) ( þ) ( À) Napadow y cols., 2006 42 (þ) ( þ) ( þ) ( À) ( þ) ( þ)( À)Yao y cols., 201243 (þ) ( þ) ( À) ( þ) ( þ) ( À)( À)Leyenda: (þ), sesgo bajo; (À), sesgo alto; (? ), no permite valoración.…”
unclassified
“…10 The efficacy of acupuncture in the management of mild-to-moderate CTS has been investigated in some studies. [11][12][13] Yang et al 14 showed that short-term acupuncture treatment was as effective as oral prednisolone in mild-to-moderate CTS. However, there are no case reports or studies on catgut-embedding therapy for CTS.…”
Section: Introductionmentioning
confidence: 99%